(untitled) (Indonesian Theological Justice Review, 2024)
Indonesia’s pluralistic society is a mosaic of diverse religious, ethnic, and cultural groups. While this diversity is a source of strength, it also presents challenges in terms of national unity and social justice. This paper explores how theology can offer pathways to justice and social cohesion in a diverse nation like Indonesia. Focusing on Islamic, Christian, Hindu, and indigenous religious teachings, the study examines how religious traditions address the challenges of living in a multi-faith society. The paper explores theological perspectives on justice, equality, and human dignity, which can help foster respect for religious pluralism and promote peaceful coexistence. It also looks at interfaith dialogues, which emphasize shared values and common goals, as a means of bridging divides. The study argues that theology can provide a moral foundation for justice by encouraging tolerance, respect for others’ rights, and the acknowledgment of cultural and religious diversity as a national asset. The paper further investigates the role of religious institutions and leaders in promoting unity and justice, particularly through advocacy for human rights, anti-discrimination efforts, and public education campaigns. Recommendations include strengthening interfaith education, encouraging collaborative social initiatives, and promoting religious tolerance through theological reflection and public discourse.